Assessment of self-efficacy and academic performance of medical students - Saxena, Manoj Kumar; Sharma, Anshuman (International Journal Of Community Medicine And Public Health, 2020)
Background: In present scenario academic self-efficacy is an important key factor to assess academic progress among students, so that their outcome in exams can be enhanced. The aim of this study was to assess academic self-efficacy among medical students according to present curriculum. Methods: This was a cross sectional study conducted among 120 students of Shyam Shah Medical College, Rewa (MP). Samples were selected from exam going students of third professional examination, either current batch or detained batch. A self-administrated, structured questionnaire was developed to collect data from the undergraduates. Assessment according to objective questions from their current syllabus was done to assess academic self-efficacy, the study adapted the questions framed by faculty members of third professional students. 200 questions from all the subjects of third year were included. Data were collected and data analysis was done by applying proper statistical tests. Results: The mean academic self-efficacy in boys was 76.03. Maximum marks obtained were 178/200 among boys and 189/200 among girls. The mean scores of all students were not significantly associated with mean scores from their academic session in college. Conclusions: The findings of this study indicate that more aged students have less academic self-efficacy as compared to their younger batch mates. Females and males were equally sincere in terms of their academic efficacy. Study pattern of medical students is curriculum based.